TRANSDISCIPLINARY PROSPECTIVE AND KNOWLEDGE ORGANIZATION: AN EPISTEMYC APPROACH TO HIGHER EDUCATION IN THE MAGALLANES REGION, CHILE - Oliva-Figueroa, Ivan G.; Molina Chavez, Walter Manuel; Quintero-Tapia, John J.; Diaz-Barrera, Nicolas S. (My University, 2018)
This paper presents the main theoretical guidelines associated with a program of scientific research on the possibilities and constraints for the development of inter-transdisciplinary dynamics in Higher Education in Chile. On this basis, the field research aim was to interpret and map the extensive regions of sense around the notion of transdisciplinarity deployed in various disciplinary fields in Higher Education in the Magallanes Region. Complementary methodological strategies were considered for the generation and analysis of information. The results suggest that the notion of inter-disciplinarity is an element of sense/direction with broad social and academic value for the informants, key participants of this research. However, this wide and distributed evaluation, is expressed in a variety of ways in terms of the elements of senses adjacent to it, in correlation with the various disciplinary fields and the role (scholars and students) that key informants play.
Keywords: interdiscipline; transdiscipline; university; complexity